2010
DOI: 10.1039/b915867g
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric stability of arsines and the determination of their oxidative products in atmospheric aerosols (PM10): evidence of the widespread phenomena of biovolatilization of arsenic

Abstract: Biovolatilisation of arsenic as their arsines in the form of AsH(3), and mono-, di and trimethylarsine has often been determined under laboratory conditions. Although environmental point sources such as landfill sites or hot springs have been characterised, only limited knowledge is available on how widespread the formation of volatile methylated arsenic compounds are in the environment. Here we studied the atmospheric stability of the different arsines and quantified their oxidation products in atmospheric pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
77
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(87 citation statements)
references
References 25 publications
8
77
2
Order By: Relevance
“…The limits of detections provided by other authors for methylated As species (e.g. DMA and MMA) lie between 0.3-0.4 ng m -3 with HG-ICP-OES detection [128], and 1.16-1.97 ng m -3 with AFS detection [123], more than an order of magnitude than those reported by [74]. Therefore, their LODs do not allow them to detect organic arsenic species at the pg m -3 level.…”
Section: High Performance Liquid Chromatography-inductively Coupled Pmentioning
confidence: 58%
See 4 more Smart Citations
“…The limits of detections provided by other authors for methylated As species (e.g. DMA and MMA) lie between 0.3-0.4 ng m -3 with HG-ICP-OES detection [128], and 1.16-1.97 ng m -3 with AFS detection [123], more than an order of magnitude than those reported by [74]. Therefore, their LODs do not allow them to detect organic arsenic species at the pg m -3 level.…”
Section: High Performance Liquid Chromatography-inductively Coupled Pmentioning
confidence: 58%
“…In view of the results of Jakob et al [74], it can be found a possible reason for the apparent discrepancy with those other analytical methodologies that have not detected methylated As in PM samples. The limits of detections provided by other authors for methylated As species (e.g.…”
Section: High Performance Liquid Chromatography-inductively Coupled Pmentioning
confidence: 60%
See 3 more Smart Citations